Effect of Sodium Ascorbate on Dentin Bonding After Two Bleaching Techniques - Briso, André Luiz Fraga [UNESP]; Rahal, V. [UNESP]; Sundfeld, Renato Herman [UNESP]; Santos, Paulo Henrique dos [UNESP]; Alexandre, R. S. [UNESP] (Operative Dentistry Inc, 2014)
The purpose of this study was to analyze the influence of 10% sodium ascorbate (SA) on the hybrid layer, resin tag length, and bond strength to dentin after bleaching. Six groups were tested: G C, control; G SA, sodium ascorbate (SA) + restoration; G CP, bleaching with carbamide peroxide (CP) + restoration; G CP+SA, bleaching with CP + SA+ restoration; G HP, bleaching with 35% hydrogen peroxide (HP) + restoration; and G HP+SA, HP + SA + restoration. After dental bleaching, the dentin was exposed and the antioxidant solution was applied to groups G SA, G CP+SA, and G HP+SA, before bonding procedures. The teeth were sectioned in the mesiodistal direction. One section was decalcified, and the specimens were embedded in paraffin and sectioned in the longitudinal direction with a thickness of 6 gm. Fifteen slices of each specimen were selected according to a systematic sample of slices with an interval proportional to the total number of slices obtained for each tooth. The specimens were stained using the Brown & Brenn method, and an optic microscope was used to analyze the hybrid layer thickness and resin tag length. The remaining tooth segment was sectioned into stick-shaped specimens and used for microtensile bond strength testing (0.5 mm/min). Statistical analysis was performed using two-way analysis of variance and Fisher test. The results for hybrid layer + tag formation (in micrometers) were G C, 13.27 Aa; G SA, 11.85 Ba; G CP, 6.84 Bb; G CP+SA, 9.02 Ab; G HP, 7.28 Bb; and G HP+SA, 9.22 Ab; bond strength results (in MPa) were G C, 49.5 Aa; G SA, 51.7 Aa; G CP, 37.16 Bb; G CP+SA, 47.69 Aa; G HP, 32.39 Ab; and G HP+SA, 39.67 Ab. Tooth bleaching with CP or HP impairs the formation of the hybrid layer and resin tags and reduces the microtensile bond strength. Statistically, the use of SA significantly increases the hybrid layer thickness and resin tag length. The microtensile bond strength values for carbamide peroxide increased, but the microtensile bond strength for hydrogen peroxide was not affected.